H kritiki mediatizacije - Amon Prodnik, Jernej (Družboslovne razprave, 2019)
In the last decade, mediatisation has established itself as a key approach in media and communication studies. Its goal is to explain the vast transformations in social relations due to the increasing power of the media. I provide a theoretical and empirical critique of the institutionalist (strong) approach to mediatisation. Empirically, the article is based on semi-structured interviews with representatives of Slovenian political parties. As is noted, the main problem of mediatisation is that it perceives the power of the media abstractly. Even though holism is advocated, authors narrowly focus on the media, without embedding it in the social totality. For a critique of the ontological, epistemological and theoretical failures, I build the article on media sociology and the political economy of communication.
Keywords: Mass media; Množični mediji; Political communication; Political parties; Politične stranke; Politično komuniciranje; Sociologija komunikacij; Sociology of communication